ESTABLECER RESPONSABILIDAD EN LA DEVOLUCIÓN DEL PAGO DE ALIMENTOS AL DETERMINARSE NEGATIVA LA PRUEBA DE ADN - GUAMAN GUAMAN, MARJORIE GISSELLA (2019)
This research paper called “ESTABLISH RESPONSIBILITY IN THE RETURN OF FOOD PAYMENT WHEN THE DNA TEST IS DETERMINED NEGATIVE”, the same that I will carry out in order to gather all the possible information identifying all the variables that attribute and harm the defendant in the case of not certifying paternity, being able to identify the damage both psychological, social and moral. The present work raised, the possibility of promptly returning the money paid by the alleged father to the pregnant woman, once her paternity had been discarded. To achieve the aforementioned purpose, try to focus on demonstrating when the obligation to provide food is born and also when it ends, and under that certainty to understand, why the restitution of an affected estate is necessary within an expedited process, in order to ensure the presumed parent the total restitution of his patrimony, without hindrances, nor affectation of any nature that this process dilate. However, it could be evidenced that the alleged parent lacked adequate evidence and, above all, a process to claim the money paid for food. The concept of pregnant women was analyzed, explaining in a general way the positive discrimination, and how the State protects and grants means of direct action to the pregnant woman, so that, in this way, she can guarantee and develop her pregnancy state optimally and full. The objective was also to know precisely, when the figure of the presumed father is born and the obligations he has in front of who is his alleged son, even giving a definition of what the alleged father means, it was explained why the principle of Higher interest is not affected, 5 since the reimbursement action is raised against the mother and not the child, in addition to the insurance child having a biological father, who must demand food. While it is true that the food provided was legitimate at the time of obtaining it, later with the DNA test, such legitimation may disappear or be distorted, and the alleged parent has the full right to return the food to those who initially demanded, that is, the mother without needing proof, more than that of the DNA to do it, and that it be done within the same process. Finally, under these premises, we will begin to develop the thesis to achieve the aforementioned purpose and be able to conclude by proposing a reform to the Organic Code for Children and Adolescents and thereby guaranteeing both parties their rights and thereby guaranteeing their well-being.